Assessment of agricultural water quality parameters in Tiruppathur district, India - Kumar, M Senthil; Ansari , A Thaminum (Bangladesh Journal of Scientific and Industrial Research, 2024)
Agricultural water sources are crucial for farming communities and impact both crop health and human consumption. This study examines seasonal variations in the physical, chemical, and bacterial properties of agricultural water sources to understand its effects on public health and agricultural productivity. Water samples were collected from various agricultural wells during different seasons throughout the year. Parameters such as pH, temperature, turbidity, TDS, phosphates, nitrates, and heavy metals were analyzed, along with bacterial content, including E. coli and total coliforms. The water quality varied significantly year-round, according to the results, because of factors like rainfall and agricultural runoff. The findings indicated that variables like rainfall and agricultural runoff caused notable annual fluctuations in the quality of the water. Recommendations include improved filtration systems and agricultural practices to ensure safe water for both farming and human use. Bangladesh J. Sci. Ind. Res. 59(4), 205-222, 2024